49.3k views
4 votes
Given that is a = 3 , b = -4 and c = -2 evaluate 3a - b / 2c + 3a - c / c - b

2 Answers

4 votes

Answer:

5.2

Explanation:

= 3a - b / 2c + 3a - c / c - b

= 3(3) - (-4) / 2(-2) + 3(3) / -2 -(-4)

= 9 + 4 / -4 + 9 / -2+4

= 13 / 5 / 2

= 13 / 5 * 2

= 2.6 * 2

= 5.2

User Vinner
by
5.5k points
3 votes

Answer:

Explanation:


(3a -b)/(2c)+(3a-c)/(c-b)=(3*3-[-4])/(2*(-2))+(3*3-[-2])/(-2-[-4])\\\\=(9+4)/(-4)+(9+2)/(-2+4)\\\\=(13)/(-4)+(11)/(2)\\\\=(-13)/(4)+(11*2)/(2*2)\\\\=(-13)/(4)+(22)/(4)\\\\=(-13+22)/(4)\\\\=(9)/(4)\\\\=2(1)/(4)

User Highstaker
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.